Penerapan Model Pembelajaran Project Based Learning Melalui Lessons Study Untuk Meningkatlkan Motivasi Belajar Siswa Pada Mata Pelajaran IPAS Kelas V Di SDN 1 Lepak - Istiani, Herlina; Ismi, Lailatul; Hasanah, Zuhriatun; Azhar, Azhar; Syraif, Muh Zahid Sarbini; Nur'aini, Nur'aini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2025)
This Lesson Study activity took place at SDN 1 Lepak which was the subject of this Lesson Study activity, namely class V. The implementation time of the Lesson Study activity lasted for 2 weeks consisting of 2 cycles of activities, where each cycle was carried out with the stages of planning, doing and seeing. The target of the Lesson Study learning is class V students of SDN 1 Lepak and the class teacher is expected to be the target so that they are accustomed to collaborating and working together in the learning process. The subject of Social Sciences is a natural learning concept and has a very broad relationship with human needs. The method of observation and data recording used in this activity during the learning process is through observation using observation sheets and video recordings. During the implementation, there was a technician who recorded using a handcam/cellphone. The images were taken in their entirety and then editing was carried out on several events that were considered important. Through the Lesson Study activity by implementing the Project Based Learning learning method, the learning motivation of class V students of SDN 1 Lepak in the subject of Social Sciences can be improved.